TOXIC EFFECTS OF CHROMIUM ON BIO-ACCUMULATION, GROWTH, OXYGEN CONSUMPTION AND METABOLIC RATE IN POSTLARVAE OF PENAEUS MONODON - Dr. Sony Mathi (Chelonian Research Foundation, 2023)
As the human population is rapidly increasing and the world has become more industrialized, the chemical wastes have increased to dangerously high levels in some areas leading to aquatic pollution. Today pollution is more threatening because many of the released pollutants degrade slowly or do not degrade at all, leading to accumulation in biota. The ocean, being so vast is constantly being used as a dumping ground which can neutralize some of these chemical wastes. Most of these effluents contain several toxic materials and among all of them, the heavy metals are considered to be more important. Chromium is one of the heavy metals reported in the industrial effluents. Although trivalent chromium (Cr III) is required in trace amounts for sugar and lipid metabolism, few cases have been reported where its complete removal from the diet has caused chromium deficiency. It is toxic in larger amounts. Hexavalent chromium (Cr VI) is toxic and carcinogenic, so that abandoned chromium production sites need environmental clean-up . Chromium levels are elevated in soil, air, water and biota in the vicinity of electroplating and metal finishing industries, municipal treatment plants, tanneries, oil drilling operations and cooling towers. There is no bio magnification of chromium in food chains but the concentrations are usually highest at the lowest trophic levels. Chromium is also reported to be present in the sediments of coastal and estuarine waters (0.8 to 2.7µg/g;[14]). As these waters are frequently used for aqua farms in coastal districts, the post larvae (PL) are prone to heavy metal toxicity, particularly chromium. Probit analysis [5] was carried out to assess the LC50 value of chromium for 24, 48, 72 and 96 hrs. The metal accumulation, growth, oxygen consumption and metabolic rate was chosen for further study on PL of P. monodon for both short term [24,48,72 and 96hrs] and long-term exposure [10,20 and 30 days]. In conclusion the PL of P. monodon are sensitive to sublethal concentration of chromium indicating increase in accumulation of chromium leads to a decrease in metabolic rate, oxygen consumption and growth. Keywords: Heavy metal toxicity, chromium, tolerance, metal accumulation, growth, oxygen consumption, crustacean, Penaeus monodon